EVALUATION OF THE LEVEL OF KNOWLEDGE OF THE ACADEMICS OF THE HEALTH AREA ABOUT THE TECHNIQUES OF USE OF PRESSURIZED INHALERS AND POWDER INHALERS (CIPEEX, 2022)
ASTHMA AND COPD ARE THE MAJOR CHRONIC RESPIRATORY DISEASES THAT ARE COMPROMISING A LARGE PART OF THE WORLD'S POPULATION. TREATMENT OF THESE COMORBIDITIES INVOLVES VARIOUS TYPES OF INHALATION DEVICES - DRY POWDER INHALERS (IPO), CONVENTIONAL NEBULIZERS (NC), METERED PRESSURIZED INHALERS (IPRE) AND MILD MIST INHALERS (INS) - WHICH DIFFER IN THEIR CHARACTERISTICS ADVANTAGES AND DISADVANTAGES. THERAPEUTIC SUCCESS OCCURS WHEN THE DRUG DELIVERED BY THESE DEVICES IS DEPOSITED PROPERLY IN THE LUNG, WHICH DEPENDS ON THE CORRECT USE OF THE DEVICES. IT IS ESSENTIAL, THEREFORE, THAT HEALTH PROFESSIONALS KNOW HOW TO TEACH THE CORRECT TECHNIQUE TO THEIR PATIENTS. THE OBJECTIVE OF THIS STUDY IS TO EVALUATE THE LEVEL OF KNOWLEDGE OF THE ACADEMICS OF A HIGHER EDUCATION INSTITUTION IN THE CITY OF ANÁPOLIS - GOIS, ENROLLED IN UNDERGRADUATE COURSES IN NURSING, PHARMACY, PHYSIOTHERAPY AND MEDICINE, REGARDING THE TECHNIQUES OF USE OF THE DEVICE AND THE POWDER INHALER. METHODOLOGICALLY, THIS IS A DESCRIPTIVE, OBSERVATIONAL AND CROSS-SECTIONAL QUANTITATIVE RESEARCH. FOR DATA COLLECTION, STANDARDIZED QUESTIONNAIRES WILL BE USED, APPLIED TO STUDENTS WHO STUDY THE LAST TWO PERIODS OF NURSING, PHARMACY, PHYSIOTHERAPY AND MEDICINE COURSES, AS WELL AS THEORETICAL AND PRACTICAL KNOWLEDGE OF THE HANDLING OF BOTH TYPES OF DEVICES. IT IS EXPECTED TO OBSERVE VARIATIONS IN THE DOMAIN OF THE TECHNIQUE OF USE AMONG PARTICIPANTS OF THE DIFFERENT COURSES, AS WELL AS IT IS SUSPECTED THAT THE DEGREE OF KNOWLEDGE REGARDING THE PRESSURIZED DEVICES IS GREATER THAN THOSE OF THE POWDER INHALER. IT IS ALSO ASSUMED THAT THEORETICAL AND PRACTICAL KNOWLEDGE IS EQUIVALENT.
Keywords: Metered pressurized inhalers. Inhalers of dust. Asthma. COPD.